Primary Cardiac Angiosarcoma: A Therapeutical Dilemma - Frota Filho,José Dario (2002)
Cardiac angiosarcomas are malignant tumors that almost invariably have a short and fatal evolution. The therapeutic approach includes surgery, chemotherapy, and radiation therapy, alone or in combination. Heart transplantation is an attractive option in nonresectable tumors, even though the current experience is still limited. However, in most patients, the diagnosis is still established late, and survival is only slightly altered by the proposed treatments, mainly due to previously existing and undetected metastases. We report a case that illustrates the therapeutic dilemma faced with this neoplasia, and we discuss the case based on a literature review.